Mindfulness in social media exposure: the pressure-reducing valve for fear of missing out and social media fatigue - Huang, Xiaoxiao (Frontiers in Psychology, 2025)
IntroductionIn the past decade, the fear of missing out (FoMO) has gained widespread attention as a prominent manifestation of the negative effects of social media. However, research on the causes, significance, and targeted methods for mitigating FoMO remains incomplete. To address this issue, this study developed an integrated model that incorporates social media exposure, perceived value, mindfulness, FoMO, and social media fatigue.MethodsUsing the partial least squares (PLS) method, this study conducted an empirical analysis of 406 Chinese social media users.ResultsFindings indicate that perceived value functions as an important antecedent of FoMO. Moreover, FoMO is not merely a conspicuous negative effect of social media exposure; it is also a key contributor to social media fatigue. Additionally, the negative associations of mindfulness with FoMO and social media fatigue underscore its effectiveness in alleviating both conditions.DiscussionTheoretically, this study demonstrates the pivotal mediating role of FoMO in the negative impacts of social media and highlights mindfulness as a promising protective factor within digital contexts. Practically, the results position mindfulness as a valuable resource for mitigating the adverse impacts of social media and fostering sustainable digital engagement.